Leveraging Technology: Enhancing Operations and Boosting EBITDA in Private Equity Owned Portfolio Companies - LIEPERT, Maximilian (Theoretical and Practical Research in Economic Fields, 2024)
The aim of the study is to determine how private equities increase the earnings before interest, taxes, depreciation and amortization (EBITDA) of their portfolio companies via tech-enabled improvement of operations. The paper analyses how private equity (PE) firms can optimize their existing business products and services to reduce non direct IT related costs. It also breaks down the application of system enhancements which increase automation and drive improvement in the PE firm context. The skillsets and involvement of C-suite managers are analysed in-depth in tandem with the role of the value creation strategy in process reengineering. Cumulatively, the paper calls on the need to initiate tech-enabled improvement of operations so as to improve revenue which is positively correlated with an influx in the EBITDA rates. In order to explore the role of tech-enabled improvement of operations in the creation of value in PE firms, the researcher relied on the use of two research paradigms namely positivism and interpretivism. The two informed the qualitative design which adopted semi-structured interviews with 29 respondents from 3 private equity firms. The data analysis process involved the identification of themes through thematic analysis. Using the constant comparative method, the researcher was able to determine the specific themes that were correlated to the responses provided and subsequent classification into the aforementioned 3 categories. The qualitative data reveals that most PE firms rely on tech-enabled improvement of operations to increase their EBITDA and value.